Roundhouse diagram based learning module development and its effect on the cognitive outcomes in the material of interaction of living things in state junior high school (SMPN) 3 Banda Aceh - Masrinur Masrinur; Cut Nurmaliah; Hasanuddin Hasanuddin (Jurnal Edubio Tropika, 2018)
This study aims to determine the feasibility of roundhouse diagrams based module and its effect on cognitive learning outcomes of learners on the interaction material of living creatures in class VII in SMP Negeri 3 Banda Aceh. Data collection is done in the even semester of the academic year 2016/2017. The approach used in the development of roundhouse diagrams based modules is the qualitative approach and the method used by Research and Development (R D) with Hannafin and Peck model. The approach used to see the effect of cognitive learning outcomes is a quantitative approach using the Quasi-Experimental method. This research was conducted in 2 classes namely VII-7 as experimental class and class VII-2 as control class. The instrument used in this research is validation sheet and learning result test. Validity feasibility validation dataanalysis by experts percentage of validity obtained 84% with validation criterion valid or can be used but need revision. Data analysis using independent sample t-test with SPSS 20 for windows at significant level 0,05. Result of t test result learners learn that t-hitung t-table (4,925 2,002). The conclusion of the study of the development of learning module based on roundhouse diagrams is feasible to be used with the average percentage validation value obtained 84%, the use of roundhouse-based learning module influences the cognitive learning outcomes in the interaction materials of living creatures in the experimental class.Keywords: Development, Module, Roundhouse Diagram and Learning Cognitive Outcomes